Segmental Arterial Mediolysis: A Vasculitis Mimic - Saira Bilal; Ayad Alkhatib; E. Blair Solow; Sanjeeva P. Kalva (Journal of Clinical Interventional Radiology ISVIR)
Background Segmental arterial mediolysis (SAM) is a rare noninflammatory vasculopathy. The purpose of this report is to describe the clinical data of six patients diagnosed with SAM, discuss key elements for diagnosis, and highlight the differences between SAM and vasculitis. We also propose a modification to the criteria developed by Kalva et al for the diagnosis of SAM. Methods This is a retrospective study approved by the Institutional Review Board and included patients diagnosed with SAM between January 2008 and December 2016. Eleven patients were identified, of whom six (four males with a median age of 59.5 years) had complete data per the guidelines proposed by Kalva et al and were thus included. Data on patient’s clinical presentation, laboratory and imaging findings, and outcomes were collected. Results Presenting symptoms included abdominal pain, flank pain, and bloody stools. Five patients had negative antinuclear antibodies (ANAs) and one had positive ANAs with negative subserologies. C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR) were normal except for an elevated CRP in two patients with organ infarction. The superior mesenteric and renal arteries were most commonly involved. The most common vascular abnormalities were dissection, pseudoaneurysm, thrombosis, and wall thickening. Two patients received endovascular repair for hepatic artery aneurysms. During the follow-up (range: 3–36 months), two patients developed a new aneurysm or dissection. Conclusion The long-term prognosis of SAM appears to be favorable. Vascular intervention is only needed for patients with impending vascular compromise. We propose that the criteria developed by Kalva et al could be modified to include patients with elevated ANA but negative subserologies and elevated CRP and ESR in the presence of organ infarction.